2021
DOI: 10.2196/22983
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of the Utilization of Facebook Groups Between Public Medical Professionals and Technical Communities to Facilitate Idea Sharing and Crowdsourcing During the COVID-19 Pandemic: Cross-sectional Observational Study

Abstract: Background: Strict social distancing measures owing to the COVID-19 pandemic have led people to rely more heavily on social media, such as Facebook groups, as a means of communication and information sharing. Multiple Facebook groups have been formed by medical professionals, laypeople, and engineering or technical groups to discuss current issues and possible solutions to the current medical crisis.Objective: This study aimed to characterize Facebook groups formed by laypersons, medical professionals, and tec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The results also showed a few residents who use the platform for entertainment and business marketing. This type of Finding can be related to those of Xun et al, (2021) and Chu et al, (2020), who discovered that Facebook is a vital social media platform for information sharing, resource sharing and professional opinions. Chu et al, (2020), added that during this time of the Covid-19 pandemic, Facebook was found to be a communication tool and that it is of value to many with its engagement efficacy.…”
Section: Findings and Discussion Nature In Which Facebook Is Being Us...mentioning
confidence: 85%
“…The results also showed a few residents who use the platform for entertainment and business marketing. This type of Finding can be related to those of Xun et al, (2021) and Chu et al, (2020), who discovered that Facebook is a vital social media platform for information sharing, resource sharing and professional opinions. Chu et al, (2020), added that during this time of the Covid-19 pandemic, Facebook was found to be a communication tool and that it is of value to many with its engagement efficacy.…”
Section: Findings and Discussion Nature In Which Facebook Is Being Us...mentioning
confidence: 85%
“…Facebook groups emerged to rapidly crowdsource collective knowledge on patient management, resources, and personal protective equipment. 108 , 109 …”
Section: Clinicalmentioning
confidence: 99%
“…Facebook groups emerged to rapidly crowdsource collective knowledge on patient management, resources, and personal protective equipment. 108,109 Information sharing also occurred across other platforms such as WhatsApp and Twitter. 110,111 In neurology, early uncertainty regarding the risk of COVID-19 to patients with multiple sclerosis on disease modifying therapy raised the need for urgent clinical decisions.…”
Section: Communities Of Practicementioning
confidence: 99%
“…In doing so, social media is the latest phenomenon of interaction among people through virtual connected networks called social networking sites [38,39]. Social media is referred to as "computer-supported social networks" (CSSNs) [40], online social networking services [41], social networking sites (SNS) [42], social websites [43], social media platforms [44], virtual communities [45], and Web 2.0 [46]. Facebook is the most popular social media platform all over the world (except in restricted countries and territories) based on user statistics, and as of January 2021, the total number of users of Facebook was 2.740 billion, followed by YouTube (2.291 billion users) (Statistica, 2021) [47].…”
Section: Literature Review-circular Economy Social Media and Re-commercementioning
confidence: 99%